Antibiotic Treatment for Chronic Rhinosinusitis: Prescription Patterns and Associations With Patient Outcome and the Sinus Microbiota - Lux, Christian A.; Wagner Mackenzie, Brett; Johnston, James; Zoing, Melissa; Biswas, Kristi; Taylor, Michael W.; Douglas, Richard G. (Frontiers in Microbiology, 2020)
Background: Chronic rhinosinusitis (CRS) is a common and debilitating inflammatory condition of the sinuses, afflicting 5% of the general population. Although antibiotics are frequently prescribed for the medical management of CRS, there is surprisingly little evidence to support their efficacy. In this meta-analysis, we aimed to establish associations between medication usage, the sinus microbiota and patients’ clinical outcomes. Methods: Antibiotic prescription patterns for the year before sample collection of 156 CRS patients, 45 disease control patients (mostly requiring septoplasty and inferior turbinate reduction) and 35 healthy control subjects were examined and correlated with previously published bacterial 16S rRNA gene amplicon data from our group. Results: The highest usage was observed among the two patient categories. Despite heavy antibiotic usage, CRS patients’ clinical outcomes as indicated by patient questionnaires and radiologic scores were similar to those patients that did not receive any antibiotics. The sinus microbiota was dominated by members of the bacterial genera Corynebacterium and Staphylococcus in all three cohorts. Bacterial community dispersion as measured by principal coordinate analysis was significantly higher in CRS patients compared to healthy control subjects, but not disease control patients. Pairwise comparisons within cohorts revealed differences in the relative 16S rRNA gene sequence abundances of the genera Staphylococcus and Lawsonella between antibiotic users and non-users. However, overall antibiotic effects were minimal and unpredictable. Conclusion: The unpredictable effects of antibiotic treatment on the sinus microbiota found in this study, together with the lack of differences in patients’ symptom scores between cohorts, do not support preoperative antibiotic treatment for CRS patients.